Sustainable visual merchandising practices: an observational study of pro-active implementation in fashion retail - Megat Zambri, Megat Amirul Ashraf; Saleh, Maarof (Universiti Teknologi MARA, Perak, 2025)
Research analyses sustainability integration in visual merchandising by using fashion retail displays as the main focus area for green practices studies. Consumer who desires environmentally responsible brands push the fashion industry to implement sustainable strategies throughout their retail design operations. This review evaluates published studies about visual merchandising applications of sustainable materials along with efficient energy systems and movable setup methods in display approaches. The analysis includes exploration of how consumer perceive sustainable retail setups and the problems retailers encounter during sustainable practice execution. The study demonstrates that sustainable visual merchandising demonstrates dual advantages as a loyalty-building technique while lowering environmental impact and promoting sustainable targets across different sectors. Future studies should analyse the enduring &impact of existing practices on sustainability together with investigations into how emerging technologies like augmented reality can minimise waste in retail display strategies.